Origin and implication of two newly identified peraluminous A-type granites in the early Paleozoic orogeny, Southeast Asia - Shu, Xu-Jie; Jiang, Wei; Wang, Dan; Cheng, Cheng; Wang, Hong-Zuo (Frontiers in Earth Science, 2023)
The amalgamation of the Yangtze and the Cathaysia Block in Neoproterozoic time led to the formation of the South China Block (SCB) and generated the Jiangnan Orogen with the occurrences of juvenile magmatic rocks. After this orogeny, a typical collisional orogen formed during the early Paleozoic period in Southeast Asia which is mainly distributed in the Wuyi-Nanling-Yunkai area in the SCB. However, the transitional time from syn-collisional compression to post-collisional extension is debatable. Here, we present new data on zircon U-Pb zircon ages, Lu-Hf isotopes, and geochemistry for the Guzhang and Shadi granites from the Nanling area, South China. Both plutons have similar zircon 238U/206Pb ages of ca. 430 Ma. Petrographic and geochemical characteristics (e.g., FeOt/(FeOt+MgO) = 0.82~0.95) indicate that both granites are peraluminous A-type, with high Ga/Al ratios (2.43 to 2.91) as well as high concentrations of Zr, Nb, Ce, Y (sum values from 327 to 527 ppm), and formation temperature (820 to 845 ℃). Shadi granite exhibit high positive εHf(t) values (clustering within 0 to +6) while Guzhang granite show relatively lower εHf(t) values (-8.7 to -2.9). Their mildly negative to positive zircon εHf(t) values are higher than that of many coeval granites and can be derived from anhydrous melting of tonalitic genesis in the middle crustal depth, with the Shadi pluton having more orthometamorphite in the source. The ages and Hf isotopic compositions of inherited zircons (εHf(t = 960 Ma) = 9.2, εHf(t = 950 Ma) = 7.3) suggest that the Neoproterozoic juvenile magmatic rocks in the Jiangnan Orogen were a significant source for these granites. We interpret these A-type granites derived at the post-collisional stage. Their occurrence indicates that the geological setting of this Paleozoic orogen shifted from compression to extension no later than 430 Ma.